Genetic diversity of androdioecious Osmanthus fragrans (Oleaceae) cultivars using microsatellite markers1. (7th May 2013) - Duan, Yifan; Wang, Xianrong; Xiang, Qibai; Liang, Lili; Li, Xuexia; Liu, Yulian; Li, Meng
Abstract : Premise of the study: For cultivar classification, identification, and genetic improvement, microsatellite markers were developed to analyze the genetic diversity of androdioecious Osmanthus fragrans cultivars. Methods and Results: Fifteen microsatellite markers were developed from sequences downloaded from the National Center for Biotechnology Information, which included two with null alleles. These primers were screened on 62 typical androdioecious O. fragrans cultivars belonging to four groups (Asiaticus, Albus, Luteus, and Aurantiacus). The number of alleles ranged from two to six, with a mean of 3.7 per locus. The observed and expected heterozygosities ranged from 0.1000 to 0.9091 and from 0.1287 to 0.9167, respectively. Results from structure analyses indicated that Asiaticus and Albus were genetically mixed, and Luteus and Aurantiacus were partially genetically differentiated. Conclusions: These markers will be useful for genetic study of androdioecious O. fragrans cultivars and facilitate cultivar classification, particularly for the cultivar groups Luteus and Aurantiacus.